Peran Partai Politik dalam Pendidikan Politik Masyarakat - Rinda Puji Lestari; Siti Qomariyah (Department of Constitutional Law, Faculty of Sharia, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Public political education is one of the roles that must be carried out by political parties as stated in Law No. 2 of 2011 concerning Political Parties. The problem is how the implementation of public political education by political parties in Batang Regency is in accordance with the provisions in Article 34 paragraph (3b) of Law Number 2 of 2011 concerning Political Parties. This type of research is field research, data collection using observation, interview, and documentation techniques. This research approach is a qualitative approach. The data analysis technique used in this research is qualitative data analysis method and then the researcher uses inductive thinking logic in drawing conclusions. The results of the study show: first, that political parties in Batang Regency have carried out their role in the political education of the people in Batang Regency. In practice this political education takes the form of activities in the form of community gatherings, seminars, consolidation, party cadre schools, and recesses interspersed with political education. Second, Political Parties in Batang Regency have implemented Article 34 paragraph (3b) of Law Number 2 of 2011, but in its implementation it has not been able to qualitatively realize the objectives contained in the Law so that public political education is less perceived by the wider community and has less impact. the results for increasing public political awareness, especially increasing the active participation of the community in general elections and local elections